2010
DOI: 10.1016/j.jss.2009.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Pharmaconutrients

Abstract: Nutritional supplementation has become the standard of care for management of critically ill patients. Traditionally, nutritional support in this patient population was intended to replete substrate deficiencies secondary to stress-induced catabolism. Recognition of the influence of certain nutrients on the immune and inflammatory response of the critically ill has led to the evolution of more sophisticated nutritional strategies and concepts. Administration of immune-enhancing formulas supplemented with a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 62 publications
0
40
0
2
Order By: Relevance
“…However, arginine supplementation could lead to unwanted vasodilation and hypotension [619,620]. Human trials of l-arginine supplementation have generally been small and reported variable effects on mortality [621][622][623][624]. The only study in septic patients showed improved survival, but had limitations in study design [623].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, arginine supplementation could lead to unwanted vasodilation and hypotension [619,620]. Human trials of l-arginine supplementation have generally been small and reported variable effects on mortality [621][622][623][624]. The only study in septic patients showed improved survival, but had limitations in study design [623].…”
mentioning
confidence: 99%
“…The only study in septic patients showed improved survival, but had limitations in study design [623]. Other studies suggested no benefit or possible harm in the subgroup of septic patients [621,624,625]. Some authors found improvement in secondary outcomes in septic patients, such as reduced infectious complications) and hospital LOS, but the relevance of these findings in the face of potential harm is unclear.…”
mentioning
confidence: 99%
“…81 The anti-inflammatory properties occur through three principle mechanisms: displacement of arachidonic acid in cell membranes, prostaglandin E3 and LTB4 production, decreased nuclear factorkappa B (NF-κB) and AP-1 activation. 81 Omega-3 FAs (ω-3 FAs) have also been shown to decrease the production of nitric oxide (NO) via downregulation of iNOS protein expression.…”
Section: Omega-3 Fatty Acids (Anti-inflammatory Nutrients)mentioning
confidence: 99%
“…81 The anti-inflammatory properties occur through three principle mechanisms: displacement of arachidonic acid in cell membranes, prostaglandin E3 and LTB4 production, decreased nuclear factorkappa B (NF-κB) and AP-1 activation. 81 Omega-3 FAs (ω-3 FAs) have also been shown to decrease the production of nitric oxide (NO) via downregulation of iNOS protein expression. 81,82 Although the inclusion of ω-3 FAs in nutrition therapy makes theoretical sense and the potential mechanisms are fairly clear, the data for the implementation of such nutrient therapy in critically ill patients are much less concrete.…”
Section: Omega-3 Fatty Acids (Anti-inflammatory Nutrients)mentioning
confidence: 99%
See 1 more Smart Citation